MANAJEMEN PROGRAM ANTI-BULLYING DALAM UPAYA MENINGKATKAN EMPATI SISWA SEKOLAH DASAR : MANAJEMEN PROGRAM ANTI-BULLYING DALAM UPAYA MENINGKATKAN EMPATI SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying at the elementary school level is an issue that affects students’ social-emotional development, including their ability to empathize. This study aims to analyze the management of an anti-bullying program to enhance students’ empathy at SDN Cikancung 06 by using the PDCA (Plan–Do–Check–Act) theory as the analytical framework. The research employed a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, and documentation, and then analyzed using data reduction, data display, and verification techniques with source and method triangulation. The results show that the implementation of the PDCA theory is reflected in all stages of the anti-bullying program management. In the Plan stage, the school conducted case mapping, formulated anti-bullying policies, and designed the integration of empathy education into the curriculum. The Do stage was carried out through anti-bullying campaigns, empathy-based learning activities, restorative approaches, and strengthened communication with parents. The Check stage included incident monitoring, assessment of students’ empathetic behavior, and regular reflection by teachers and the anti-bullying team. Subsequently, the Act stage produced follow-up actions such as revising reporting SOPs, adding guidance programs, and strengthening coordination among school stakeholders. Overall, the application of the PDCA cycle proved effective in helping the school manage the anti-bullying program systematically and sustainably, thus contributing to increased student empathy and the creation of a safe and conducive learning environment. These findings affirm that PDCA can serve as an effective model for managing character-based educational programs